CONTROL OF FLOWER PATHOGEN ACTIVITIES OF SOYBEAN PLANTS IN STRAIN COCONUTION PSEUDOMONAS SP. AND BACILLUS SP. WITH BRADYRHIZOBIUMJAPONICUM - Nunung Sulistyani; Aris Tri Wahyudi; Giyanto Giyanto (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2013)
Plant growth promoting rhizobacteria (PGPR) is a bacterial colonization of plant roots that can stimulate the growth of plants directly or indirectly. The PGPR mechanism indirectly results in plant growth as it suppresses the growth of phytopathogen. This study aims to determine the ability of Pseudomonas sp. and Bacillus sp. in controlling the pathogenic root fungal pathogenic fungi. Isolates in this study were Pseudomonas sp. Crb 3, Crb 17, Crb 17i, Crb 68 and Bacillus sp. Cr 24, Cr 44, Cr 66 co-inoculated with B. japonicum in soybean plants in greenhouses. An antagonistic activity test was performed on all isolates and all isolates showed no antagonistic activity. Treatment of combination of strain Pseudomonas sp.Crb 17, Crb 17i and Bacillus sp. Cr 24 inoculated with B. japonicum suppresses the growth of root rot fungi and increases peroxidase. Therefore, Pseudomonas sp. Crb 17, Crb 17i and Bacillus sp. Cr 24 can be used as a biocontrol agent for pathogenic fungi causing plant root disease.